Similarities and Differences in Posture During Simulated Order Picking in Real Life and Virtual Reality - Friemert, Daniel; Saala, Florian; Hartmann, Ulrich; Ellegast, Rolf (Digital Human Modeling. Applications in Health, Safety, Ergonomics, and Risk Management, 2018)
The study we present in this article investigates to which extent a virtual reality (VR) environment can replace a real physical mock-up for ergonomic analysis. For this purpose, we built both a physical mockup of a real order picking workplace (RE) and a corresponding VR environment using head mounted displays and haptic controller devices. We used state-of-the-art motion capturing tools in order to track the postures of our subjects during their picking activities in both conditions (VR and RE). The comparison of the measurements and the statistical analyses reveal the similarities and differences of movements and postures. For instance, a very high resemblance in posture was found in the thoracic spine lateral inclination, the head lateral inclination and the back flexion. Furthermore, we found that lateral movements and ranges of motion are very similar under all tested circumstances. However, looking at the sagittal head and neck flexion measurements, statistical analysis categorized a large majority of the data as dissimilar. Significantly higher sagittal head inclination angles are measured in VR. These differences might be caused by systemic traits connected to the VR environment, for example missing haptics or constrained field of view. Despite the fact that our VR environment could not perfectly mimic the real workplace, our study encourages the view that VR-HMDs have the potential to supplement physical mockups for ergonomic workload analysis or even become a real alternative once these traits are taken into account.